Embolizing Massive Right Atrial Thrombus in a HIV-Infected Patient - Piruthiviraj Natarajan MD; Fowrooz Joolhar MD; Sudhagar Thangarasu MD; Ayham Aboeed MD; Theingi Tiffany Win MD; Everardo Cobos MD (SAGE Publishing, 2018)
The risk of thromboembolism is increased when associated with the human immunodeficiency viral (HIV) infection. Various factors are involved in promoting thrombosis, and the presence of a patent foramen ovale augments the potential for a paradoxical embolism. We describe the case of a 56-year-old man receiving antiretroviral therapy with features of right heart failure and pulmonary embolism. Due to the high incidence of life-threatening thromboembolism in the HIV-infected group, the need for long-term anticoagulation has to be evaluated.